2014
DOI: 10.1007/s12217-013-9356-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Simulated Microgravity on the Activity of Regulatory Enzymes of Glycolysis and Gluconeogenesis in Mice Liver

Abstract: Gravity supports all the life activities present on earth. Microgravity environments have effect on the biological functions and physiological status of an individual. The present study was undertaken to investigate the effect of simulated microgravity on important regulatory enzymes of carbohydrate metabolism in liver using HLS mice model. Following hind limb unloading of mice for 11 days the animal's average body weights were found to be not different, while the liver weights were decreased and found to be s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
(27 reference statements)
1
6
0
Order By: Relevance
“…The cytotoxic effect of aqueous areca nut extract on A549 cells was measured by LDH assay as described earlier with slight modification (Decker and Lohmann-Matthes, 1988;Ramirez et al, 2014). LDH in media was quantified by a coupled enzymatic reaction in which LDH catalyzes the conversion of lactate to pyruvate via NAD+ reduction to NADH.…”
Section: Lactate Dehydrogenase (Ldh) Assaymentioning
confidence: 99%
“…The cytotoxic effect of aqueous areca nut extract on A549 cells was measured by LDH assay as described earlier with slight modification (Decker and Lohmann-Matthes, 1988;Ramirez et al, 2014). LDH in media was quantified by a coupled enzymatic reaction in which LDH catalyzes the conversion of lactate to pyruvate via NAD+ reduction to NADH.…”
Section: Lactate Dehydrogenase (Ldh) Assaymentioning
confidence: 99%
“…Cell-free supernatant (50 μl) from each well was transferred to a 96-wells plate in triplicates and 150 μl of LDH-assay reaction mixture was added. Once the color was developed the optical density was measured at a wavelength of 490 nm using a microplate reader (Ramirez et al, 2014).…”
Section: Lactate Dehydrogenase Assay (Ldh)mentioning
confidence: 99%
“…Glycolysis is a common way for all organisms to extract energy from glucose, and gluconeogenesis provides a source for new glucose molecules. Glucose is produced from small carbohydrate substrates such as pyruvate, lactic acid, glycerin, and glucose amino acids, and to synthesize glucose from simple starting materials to meet the needs of various tissues [26][27]. And In our study, when BSS occurred, the model group showed signi cant upregulation of pyruvate, suggesting that glucose metabolism disorders may occur.…”
Section: Discussionmentioning
confidence: 64%